Seychelles : Climate Change Policy Assessment. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper takes stock of Seychelles' plans to manage climate change, from the perspective of its macroeconomic implications. It suggests macro-relevant reforms that could strengthen the plans' likelihood of success. It highlights high public awareness and a body of existing sustainable development planning, which puts Seychelles several steps ahead toward preparedness. Next steps would be to ensure that climate change planning is integrated with the forthcoming National Development Plan. Disaster preparedness is a relatively strong point, but there is much still to be done-from improving warning systems to resilience building to contingency financing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet